Morphohistogenesis of proventriculus in fowl (Gallus domesticus) - Verma, D; Malik, M R; Parmar, M L; Taluja, J S (The Indian Journal of Animal Sciences, 2012)
The proventriculus of fowl attained its elongated, spindle-shape in the embryos of 12 days. It was situated slightly left to the beart and left lobe of the liver. The length and width of proventriculus ranged from 6.00 to 53.20 mm and 3.62 to 25.00 mm from day 12 of incubation to 32 weeks of post-hatch age, respectively, and cross sectional area from 10.40 to 439.00 mm from day 0 to 32 weeks of age. The growth spurts of length and width revealed their maximum (125.00 and 55.55%) values in the chicks of 19 days of incubation to day 0. The CS area revealed its maximum (306.50%) and minimum (8.10%) increase in the chicks of 4-8 and 8-16 weeks of age respectively. The total wall thickness of the proventriculusaried from 823.00 to 3 128.00 Âµm between day 12 of incubation and 32 weeks of post-hatched age. The tunica mucosa was thick and contributed maximum (77.41-87.76%) to the total wall thickness to the tunica muscularis (8.76-1 4.91 %) in different age groups. The lamina propria contained gastric glands on day 12 of incubation onward. The external layer of tunica muscularis was thinner than the inner layer.